Attitudes and Skills in Basic Life Support after Two Types of Training: Traditional vs. Gamification, of Compulsory Secondary Education Students: A Simulation Study - Adrián Rodríguez-García; Giovanna Ruiz-García; Rubén Navarro-Patón; Marcos Mecías-Calvo (MDPI AG, 2024)
It is recommended to implement the teaching of Basic Life Support (BLS) in schools; however, studies on the best training method are limited and have been a priority in recent years. The objective of this study was to analyze the attitudes and practical skills learned during BLS training using a gamified proposal. A comparative study was carried out, consisting of Compulsory Secondary Education students [control group (CG; classical teaching) and experimental group (EG; gamified proposal)]. The instruments used were the CPR and AED action sequence observation sheet, data from the Laerdal Resusci Anne manikin and AED and Attitude Questionnaire towards Basic Life Support and the Use of the Automated External Defibrillator. Sixty-eight students (33 girls) with a mean age of 13.91 ± 0.70 years were recruited. Results were significantly better in the EG (n = 37) [i.e., breathing control (p = 0.037); call to emergency services (p = 0.049); mean compression depth (p = 0.001); self-confidence (p = 0.006); intention to perform BLS and AED (p = 0.002)]; and significantly better in the CG (n = 31) [Total percentage of CPR (p < 0.001); percentage of correct compression (p < 0.001); time to apply effective shock with AED (p < 0.001); demotivation (p = 0.005). We can conclude that the group that was trained with the training method through the gamified proposal presents better intentions and attitudes to act in the event of cardiac arrest than those of the classic method. This training method allows for similar results in terms of CPR and AED skills to classical teaching, so it should be taken into account as a method for teaching BLS to secondary education students.